Variations in Occipitocervical and Cervicothoracic Alignment Parameters Based on Age: A Prospective Study of Asymptomatic Volunteers Using Full-Body Radiographs. Issue 23 (1st December 2016) - Iyer, Sravisht; Lenke, Lawrence G.; Nemani, Venu M.; Fu, Michael; Shifflett, Grant D.; Albert, Todd J.; Sides, Brenda A.; Metz, Lionel N.; Cunningham, Matthew E.; Kim, Han Jo
Abstract : Study Design: Cross-Sectional Cohort Study Objective: To describe age-stratified normative values of novel occipitocervical, cervical, and cervicothoracic alignment parameters. Summary of Background Data: Full-body radiographic images obtained without stitching or vertical distortion represent an ideal method to evaluate occipitocervical alignment and horizontal gaze. Methods: One hundred twenty adults with no back or neck symptoms were recruited. Age, sex, body mass index, Neck Disability Index (NDI), and Oswestry Disability Index scores were recorded. Radiographic parameters measured included: center sacral vertebral line, chin brow vertical angle (CBVA), orbital tilt (OrT), orbital slope, occipital slope (OS), occipital incidence, occiput-C2 (O-C2) lordosis, cervical lordosis (C2-C7, CL), T1 slope (TS), neck tilt, thoracic inlet angle (TIA), cervicothoracic kyphosis (C6-T4), and C2-C7 sagittal vertical axis (C2-7 SVA). Interobserver reliability was calculated for all measurements (intraclass correlation coefficient, ICC). A Pearson correlation was used to determine relationships between variables. Results: A total of 115 patients were analyzed; average age as 50.1 years (range 22–78). All measured variables had an ICC >0.6. CL ( r = −0.33, P < 0.001), TS ( r = 0.42, P < 0.001), TIA ( r = 0.24, P = 0.010), and C7 SVA ( r = 0.48, P < 0.001) all increased with age. OrT ( r = −0.88, P < 0.001) and OS ( r = 0.73, P < 0.001) were both strongly correlated with CBVA and each other ( r = −0.83, P ⩽ 0.001). Both measures were also correlated with the C2-C7 SVA (OrT, r = 0.41, P < 0.001; OS, r = −0.29, P = 0.002) and O-C2 angle (OrT, r = 0.46, P < 0.001; OS, r = −0.28, P = 0.003). C6-T4 angulations was negatively correlated with NDI scores in this population ( r = −0.25, P = 0.007). Conclusion: We present age-based normative values for occipitocervical, cervicothoracic, and cervical alignment parameters using a novel biplanar radiographic imaging technique. We introduce measures of craniocervical alignment that might provide surgeons with an intuitive way to account for the position of the orbit when planning cervical deformity correction. Level of Evidence: 4